Analisa Tingkat Keselamatan Lalu Lintas Pada Simpang Empat Marene Menggunakan Metode Traffic Conflict Technique (TCT) - Setiawan, Ari; Dwiretnani, Annisaa; Fajri, Muhammad (Jurnal Civronlit Unbari, 2023)
The basic concept of transportation is to facilitate mobilization from the Point of origin towards to the point of destination. One of element of that is quite important in transportation users that refer to the riders. It is need to be done a research about that to improve riding safety.This study used Traffic Conflict Technique method (TCT) Near-Missed Accident discovered and developed by Lund Swedish University. TCT refers to the relationship between road user behavior in the event of an accident generally be able to produce classifications Related to factors that cause a conflict or accident. This research conducted in Jambi City, at the junction connecting Jln. Sentot Ali Basa-Lrg. Marene-Jln. Raya Kasang Pudak-Jln. Lingkar Timur II. The location is quite representative with a focus of research, because the intersection has a fairly heavy volume of traffic flow, so that sometimes traffic jams and past violations often occur to the other cross.Based on results, the Average of Time to Accident (TA) that needed to evade or evasive for about 0,1 seconds; Whole conflict that is occurs included in the classification of Serious Conflict; the type of conflict that occurs is crossing and, from four conflicts that occurred at the location research on the majority of road users who are often involved in conflict Bentor riders who subsequently fall into the category of vehicle type motorized or MC.